Experimental investigation of orientation and geometry effect on additive manufactured aluminium LED heat sinks under natural convection. (1st June 2021) - Tucker, Robert; Khatamifar, Mehdi; Lin, Wenxian; McDonald, Kyle
Abstract: The continued adaptation of light-emitting diodes (LEDs) presents challenges for heat dissipation. LEDs are considered to be high power density devices, as such effective thermal management is imperative for extended usage. In this study, new design considerations such as adapting middle fin, fin height gradient towards the centre of the heat sink, along with fin perforations and a spiral cut out of the central pillar have been incorporated into heat sinks to assist convection. The heat sinks were manufactured out of aluminium alloy (AlSi10Mg) using the selective laser melting (SLM) method. The effects of orientation on the heat transfer of different heat sink geometries were experimentally studied under natural convection conditions. The performance of six different geometries with 6, 8 and 10 long fins (6LF, 8LF and 10LF) with and without middle fins were evaluated under three different heat flux conditions (471.57 W / m 2, 943.14 W / m 2 and 1257.52 W / m 2 ) for 10 different orientation angles (0°–90°). The higher fin density heat sinks are found to have lower orientation dependency. The convective fluid flow of the higher fin density geometries is significantly hindered by the overlapping of thermal boundary layers. The increase in the Rayleigh number has the most significant effect on the 6LF heat sink. The overall Nusselt number correlations for the 6LF, 8LF and 10LF heat sinks with short fins are 0.2748 Ra 0.3425, 0.3868 Ra 0.2747 and 0.3317 Ra 0.2708, respectively. Removing short fins improved heat transfer rate for all heat sinks.